The restorative effects of nature exposure on the self-regulation resources in mentally fatigued soccer players: a randomized controlled trial - Soh, Kim Geok; Sun, He; Mohammadi, Alireza; Toumi, Zakaria; Runzhen, Chang; Jun, Jiang (Department of Sports Medicine, Medical Faculty of Uludag University, 2024)
Interventions involving exposure to nature can increase self-regulatory resources. However, this improvement has never been examined in mentally fatigued soccer players who have insufficient resources to self-regulate and maintain specific performances. The present study aims to investigate how exposure to nature influences the self-regulation capability of university soccer players who are mentally fatigued. The participants aged 18-24 years (M = 20.73 ± 2.00), with an average training duration of 5.14 ± 1.31 years, were randomly divided into six different groups (three experimental groups and three control groups). Each experimental group was compared with its corresponding control group using three different intervention durations: 4.17 min, 8.33 min, and 12.50 min. A forty-five-minute Stroop task was used to induce mental fatigue, followed by the intervention. The indicators of self-regulation, both physiological (heart rate variability, or HRV) and psychological (competitive state anxiety), were recorded. Experimental Group 3 (12.50 min intervention) only showed significant improvement in HRV (p = 0.008, d = 0.93), competitive state anxiety (cognitive and somatic anxiety p = 0.019, d = 0.86; state confidence p = 0.041, d = 0.797) compared to control group 3. Nature exposure significantly improves selfregulation in mentally fatigued soccer players. Specifically, the 12.50 min intervention showed the greatest improvements in both HRV and competitive state anxiety, suggesting that a longer duration of nature exposure enhances mental restoration more effectively.